Successful laparoscopic partial gastrectomy and spleen-preserving distal pancreatectomy for gastric duplication cyst connecting with the pancreatic tail. (2018) - Kawaida, Hiromichi; Kimura, Ayako; Watanabe, Mitsuaki; Akaike, Hidenori; Hosomura, Naohiro; Kawaguchi, Yoshihiko; Amemiya, Hidetake; Sudo, Makoto; Kono, Hiroshi; Matsuda, Masanori; Fujii, Hideki; Ichikawa, Daisuke; et al.
Highlights: Gastric duplication cyst(GDC) contiguous with the stomach and pancreatic tail is extremely rare. GDCs are usually diagnosed at a younger age. In adults, they are very rare disease and the diagnosis may be difficult. Surgical resection is considered to be the best treatment due to the difficulty of diagnosis. Laparoscopic surgery is less invasive and should be selected whenever possible. Abstract: Introduction: Gastrointestinal duplication cyst is a congenital rare disease that may occur in any region from mouth to anus. Among them, gastric duplication cysts are very rare. Case report: Here we report A 23-year-old Japanese man who visited our hospital to evaluate an abdominal tumor. Abdominal computed tomography showed a well-circumscribed homogenous low-density mass measuring 6.2 × 6.0 cm between the pancreatic tail and the upper posterior wall on the gastric greater curvature, and the mass seemed to originate from the pancreatic tail. We found intraoperatively that the mass adhered to the stomach and pancreatic tail strongly, so we performed laparoscopic partial gastrectomy and spleen-preserving distal pancreatectomy. Pathological findings showed that the lining epithelium of the cystic mass consisted of the gastric foveolar epithelium with fundic glands. Furthermore, the pancreatic tissue of the pancreatic tail and the muscular layer of the cystic mass were intermingled. Discussion: GDCs are usually diagnosed at a younger age and in adults, they are very rare. Therefore, surgical resection is considered to be the best treatment due to the difficulty of diagnosis, and also that it mimics a pancreatic cystic tumor, and malignant transformation. Complete resection of the cyst is the ideal technique and laparoscopic surgery should be selected whenever possible. Conclusion: We experienced a case of GDC continuous to both stomach and pancreatic tail. Laparoscopic surgery is safety and useful even if GDC is continuous with both the stomach and the pancreas.